KRIBAGOR (Fried Spinach Chips) is a Healthy and Nutritional Snack and Can Overcome Anemia - Marselina Yuniarti; Refni Lujung; Norvinlia Eti; Reineldis Elsidianastika Trisnawati (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Spinach is a type of vegetable that is highly nutritious and favored by all levels of society. The iron content in spinach is very high compared to other vegetables, so it is very good for consumption by people with anemia and pregnant women. Spinach can also be used by mothers as a solution for children who do not like to eat vegetables, by introducing spinach chips to these children. This PkM activity aims to increase the yield of spinach plants by farmers and the community can use spinach to make healthy and nutritious snacks for children and adults seen from the many benefits of spinach chips so it is very good if used as a side business for the community so that they can help the economy. The outputs of this PkM are creating Spinach Chips products that are rich in nutritional value, increasing the creativity of students and the community in processing spinach leaves into Spinach Chips, and printing an easy generation that can compete in the entrepreneurial field.